Pengaruh Kepercayaan Manajerial, Orientasi Jangka Pendek, dan Iklim Kerja Etis Terhadap Senjangan Anggaran - Tanadi, Clara Yunneke; Mimba, Ni Putu Sri Harta (E-Jurnal Akuntansi; Vol 30 No 3 (2020), 2020)
The research aims to examine the effect of managerial trust, short-term orientation, and ethical work climate on budgetary slack. Budgetary slack is the difference between budgeted revenues and expenses with estimates that can be obtained. The location of the study was conducted at the Office of Labor and Energy of Mineral Resources in Bali Province. The sampling method used is nonprobability sampling by census or total sampling. Data collection methods used survey methods by distributing questionnaires with 80 respondents. The data analysis technique used is multiple linear regression analysis. The results obtained are managerial trust negatively affect budgetary slack, short-term orientation has a positive effect on budgetary slack, and ethical work climate has no effect on budgetary slack. Keywords: Managerial Trust; Short-term Orientation; Ethical Work Climate; Budgetary Slack.